2021
DOI: 10.3349/ymj.2021.62.2.109
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Postoperative Chemotherapy on pT1bN0 and pT2N0 Gastric Cancer Patients with Risk Factors: An International Dual-Center Analysis

Abstract: Purpose This study aimed to investigate the effectiveness of postoperative chemotherapy in pT1bN0 and pT2N0 gastric cancer patients with high risk factors. Materials and Methods Clinicopathological data of gastric cancer patients, who had undergone gastrectomy in high volume centers in Korea and China and were finally diagnosed with pT1bN0 and pT2N0 between 2006 and 2010, were analyzed retrospectively. Survival analyses stratified by risk factors and multivariable analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Zheng et al 20 reported that adjuvant CT had no effect on the prognosis in T2N0 patients. Consistent with our ndings, a recent retrospective study comprising only stage IB GC showed that the OS rates in the adjuvant CT group were 95.1% compared with 93.3% in surgery alone group, with no signi cant difference detected 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Zheng et al 20 reported that adjuvant CT had no effect on the prognosis in T2N0 patients. Consistent with our ndings, a recent retrospective study comprising only stage IB GC showed that the OS rates in the adjuvant CT group were 95.1% compared with 93.3% in surgery alone group, with no signi cant difference detected 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Subgroup analyses also demonstrated that postoperative chemotherapy had no survival benefit in the 5-year OS rates of patients with stage ypT1N0 or ypT2N0 gastric cancer ( p = 0.786; p = 0.551). Although adjuvant chemotherapy is not recommended for gastric cancer patients with pT1-2N0 stage in many guidelines, there have been studies drawing conclusions that postoperative chemotherapy could offer survival benefits to these pT2N0 patients with risk factors, such as larger tumor diameter, lymphovascular invasion, suboptimal lymphadenectomy, and poor differentiation [ 28 – 30 ]. Herein, we were inspired by these findings and speculated that whether postoperative chemotherapy could offer survival benefit to stage ypT1-2N0 gastric cancer patients who had risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] and Yang et al . [ 35 ] revealed that stage IB GC patients who received AC did not have prolonged survival. However, in a retrospective analysis of 1,687 patients, In et al .…”
Section: Discussionmentioning
confidence: 99%